What Darwin didn't know - Leroi, Armand Marie; Lambert, Tim (London : BBC Productions, 2009)
Marking the 150th anniversary of Darwin's epoch defining On the Origin of Species, this film reveals how the advance of science has proved him right. Darwin gave us the most sensational idea in biology: evolution by natural selection. But even he knew that it came with difficulties and many of them.
Executive producer, Anne Laking ; editor, Richard Wilkinson
Host, Armand Marie Leroi.
dvd format
Keywords: Darwin, Charles, -- 1809-1882. -- On the origin of species; Evolution (Biology) -- History; Natural selection -- History